The effects of oil price uncertainty on the macroeconomy - Soojin Jo (Bank of Canada, 2012)
This paper investigates the effect of oil price uncertainty on real economic activity using a quarterly VAR with stochastic volatility in mean. Stochastic volatility allows oil price uncertainty to vary separately from changes in the level of oil prices, and thus the impact of oil price uncertainty can be examined in a more flexible yet tractable way. In addition, this paper substantially improves on the recovery of a historical uncertainty series by incorporating an additional uncertainty indicator, i.e., a realized volatility series from daily oil price data, into the estimation process. The estimation results show that an oil price uncertainty shock alone has negative effects on world industrial production.
Keywords: E32; C32; Q43; 330; Business fluctuations and cycles; Econometric and statistical methods